2011
DOI: 10.1186/1741-7015-9-128
|View full text |Cite
|
Sign up to set email alerts
|

Brief psychosocial education, not core stabilization, reduced incidence of low back pain: results from the Prevention of Low Back Pain in the Military (POLM) cluster randomized trial

Abstract: BackgroundEffective strategies for the primary prevention of low back pain (LBP) remain elusive with few large-scale clinical trials investigating exercise and education approaches. The purpose of this trial was to determine whether core stabilization alone or in combination with psychosocial education prevented incidence of low back pain in comparison to traditional lumbar exercise.MethodsThe Prevention of Low Back Pain in the Military study was a cluster randomized clinical study with four intervention arms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 43 publications
0
53
0
3
Order By: Relevance
“…However, implementing screening measures based on psychosocial factors may help guide practice in physical therapy treatment. These efforts may then be further extended to improve treatment of low back pain in different patient populations at risk for developing chronic pain with concomitant psychosocial factors, such as those in military settings (14,60). …”
Section: Discussionmentioning
confidence: 99%
“…However, implementing screening measures based on psychosocial factors may help guide practice in physical therapy treatment. These efforts may then be further extended to improve treatment of low back pain in different patient populations at risk for developing chronic pain with concomitant psychosocial factors, such as those in military settings (14,60). …”
Section: Discussionmentioning
confidence: 99%
“…POLM trial results indicated that psychosocial education was found to be preventative of seeking healthcare for LBP [17]. This study reports on a secondary aim of the POLM trial which was to determine what factors were predictive of self-reported LBP for Soldiers that responded to a web-based or phone survey tools.…”
Section: Methodsmentioning
confidence: 99%
“…The Personalized Psychological Education interventions follow what has been used in low back pain clinical trials [65–68] and key principles in psychologically informed interventions [69]. These principles are not specific to the anatomical region of pain, for example there is a clinical trial of cognitive behavioral treatment for reducing catastrophizing in individuals with chronic headache [70].…”
Section: Methodsmentioning
confidence: 99%